2015
DOI: 10.1007/s00253-015-6529-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide investigation of the genes involved in nicotine metabolism in Pseudomonas putida J5 by Tn5 transposon mutagenesis

Abstract: Pseudomonas putida J5 is an efficient nicotine-degrading bacterial strain isolated from the tobacco rhizosphere. We successfully performed a comprehensive whole-genome analysis of nicotine metabolism-associated genes by Tn5 transposon mutagenesis in P. putida J5. A total of 18 mutants with unique insertions screened from 16,324 Tn5-transformants failed to use nicotine as the sole carbon source. Flanking sequences of the Tn5 transposon were cloned with a shotgun method from all of the nicotine-growth-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Thus, the function of NicA1 remains unclear, and NicA2 is likely the true nicotine oxidase. The ndaA gene in P. putida J5, required for degradation of nicotine by that organism, codes for a protein that is 99% identical in sequence to that of NicA2 [52], so that NdaA is also likely to be a nicotine oxidase. The structure of NicA2 was recently determined, showing that the protein is a member of the MAO family with the same overall structure as LHNO (Fig.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the function of NicA1 remains unclear, and NicA2 is likely the true nicotine oxidase. The ndaA gene in P. putida J5, required for degradation of nicotine by that organism, codes for a protein that is 99% identical in sequence to that of NicA2 [52], so that NdaA is also likely to be a nicotine oxidase. The structure of NicA2 was recently determined, showing that the protein is a member of the MAO family with the same overall structure as LHNO (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…Both are FAD-containing enzymes whose sequences place them in the MAO family of flavoproteins. The sequence of NdaC from P. putida J5 is identical to that of Pnao, although the protein itself has not been characterized, and loss of ndaC eliminates the ability of cells to metabolize pseudooxynicotine [52]. In the case of Pnao the source of the oxygen in the 3-succinoylsemialdehyde pyridine product has been shown to be water [55], establishing the reaction catalyzed by the enzyme as shown in Scheme 9, with the hydrolytic step being nonenzymatic.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As a powerful approach for functional gene analysis, DNA transposition has been performed in multifarious bacteria, including Listeria monocytogenes ( Chang et al, 2012 ), Riemerella anatipestifer ( Wang X. et al, 2014 ), Pseudomonas putida ( Xia et al, 2015 ) and Salmonella typhimurium ( Sahu et al, 2013 ), to ascertain genetic determinants. In this study, we identified 24 biofilm-associated genes based on a library of 1030 mutant colonies of A. hydrophila , among which 14 genes were shown to enhance biofilm formation and 10 were involved in reducing biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…nic22 [23], Pseudomonas sp. ZJUSKD [24], Pseudomonas putida J5 [25], Pseudomonas putida HF-1 [26], Pseudomonas plecoglossicida TND35 [27], Pseudomonas sp. HZN6 [28,29,30], Pseudomonas geniculata N1 [31], Shinella sp.…”
Section: Figurementioning
confidence: 99%